Pengaruh Environmental Advertisement terhadap Green Purchase Intention melalui Environmental Awareness sebagai Variabel Intervening (Studi Pada Uniqlo di Kota Solo) - Endah Kusmartiyah; Arry Widodo (Ekonomis: Journal of Economics and Business, 2023)
The fashion industry is the third largest industry in the world after the automotive and technology industries which can cause landfill waste because more than 150 billion clothes are produced in the world every year. The fast fashion industry generates enormous waste and pressure on the environment. Uniqlo, a clothing retailer from Japan which is under the auspices of a company called Fast Retailing, argues that they are part of this fast fashion business model by creating several innovations to protect the environment in the future. This is expected to increase awareness of the environment through several forms of advertising created by Uniqlo in order to form consumer intentions to buy Uniqlo products. This research was conducted to determine the effect of environmental advertising on green buying intentions with environmental awareness as an intervention variable at Uniqlo in Solo. The research method used in this study is a quantitative method with Structural Equation Modeling (SEM) analysis techniques using SMART PLS software. The sampling method used was purposive sampling with 100 respondents. Each of the variables in this criterion has a good proportion of environmental advertising with a value variable of 78.73%, an environmental awareness variable of 79.9% and an environmentally friendly purchase intention variable of 82.2% good judgment from consumers. Environmental advertising has a positive and significant effect on green purchase intention with environmental awareness as an intervening variable with a contribution of 79%.